Sistem Pendukung Keputusan Penentuan Produk Terbaik Menggunakan Metode Preference Selection Index - Annida Purnamawati; Monikka Nur Winarto; Daniati Uki Eka Saputri (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2023)
The purpose of this research is to assist the company in determining the best product to use based on production results so that it can increase customer satisfaction in using and consuming products sold using the preference selection index method. The application of the preference selection index method in determining the best product will result in a comparison of the values of all product data produced in the 1st quarter period. So that the developed decision support system can determine the best product according to predetermined criteria. The calculation of determining the best product using the preference selection index shows that the results of calculating the final value of the 1st best product get a final score of 0.9495 obtained for the Original Banana Chips product, the 2nd best product gets a final score of 0.8969 obtained for the Banana Chips product Balado Hijau and the 3rd best product with a final score of 0.8783 was obtained for the Milk Banana Chips product.